Big data analytics with applications in insider threat detection - Thuraisingham, Bhavani; Parveen, Pallabi; Masud, Mohammad Mehedy; Khan, Latifur (CRC Press, 2018)
Today's malware mutates randomly to avoid detection, but reactively adaptive malware is more intelligent, learning and adapting to new computer defenses on the fly. Using the same algorithms that antivirus software uses to detect viruses, reactively adaptive malware deploys those algorithms to outwit antivirus defenses and to go undetected. This book provides details of the tools, the types of malware the tools will detect, implementation of the tools in a cloud computing framework and the applications for insider threat detection.